Conceptualizing a research framework for tour operators' motivation and practices in responsible rural tourism development - Tay, Kai Xin; Kim, Jennifer Lian Chan; Nair, Vikneswaran; Ramachandran, Sridar (2013)
Sustainability is widely discussed by researchers and also by tourism stakeholders for nearly three decades. This paper reviews the motivations of tour operators and their practices in responsible rural tourism development as well as the challenges and barriers faced. The paper also proposes a conceptual framework based on push and pull forces factors and organizational benefits as motivators to trigger the practice of responsible tourism development amongst tour operators in rural tourism destinations, while minimizing negative environmental, social and economic impacts.